Trade, Capital Accumulation and Structural Unemployment: An Empirical Study of the Singapore Economy - KEE, Hiau Looi (Institutional Knowledge at Singapore Management University, 2005)
This paper studies the factors responsible for the secular decline of Singapore's unemployment rate over the period 1966-2000 in an environment of low and stable inflation rates. We introduce wage bargaining and unions into a specific-factors, two-sector economy with an export sector and a non-tradable sector to obtain an endogenous natural unemployment rate. Increases in the relative export price and capital stock in the export sector are predicted to reduce structural unemployment. These hypotheses could not be rejected based on structural estimations and co-integration regressions. Empirically, capital accumulation in the export sector explains most of the decline in Singapore's unemployment rate.